Children: plural noun - Deborah Thomé Sayão (Universidade Federal de Santa Catarina, 2002)
When we allow children to hear or see with whom we work, teachers and professors, we are faced with unusual situations, with the unexpected, the unforeseen. Often unable to provide answers to questions and in some cases, we do not know how to intervene in a given situation. So often, we pretend that we do not see ... In addition, the involvement that has come with cases of initial or continuing training for professionals working with children still small, have placed issues like "who are the children?" In the center of discussions.